Women's experiences and outcomes of abortion care in sub-Saharan countries: A mixed methods systematic review protocol. - Negash Wakgari; Gizachew A Tessema; Stuart J Watson; Delayehu Bekele; Zoe Bradfield (PLoS ONE)
Introduction Abortion care experiences encompass various aspects, including women's decision-making capability, physical and emotional experiences, service provision, and post-abortion experiences. The lack of woman-centred and respectful abortion services, influenced by stigma and restrictive abortion laws in certain contexts, poses a public health concern. These challenges may lead to variations in women's experiences and care outcomes, potentially resulting in adverse physical, psychological, and emotional outcomes for individuals seeking abortions. Therefore, this systematic review aims to synthesise the available evidence on women's abortion care experiences and outcomes in sub-Saharan Africa published from 2010 onwards. Methods Eight databases including Medline, Embase, Scopus, CINAHL, Cochrane Library, Psych-Info, Web of Science, and Global Health will be searched using subject headings and specific keywords related to women's abortion care experiences, abortion care outcomes, and its measurement. Predetermined criteria will be used to select studies that meet the review's inclusion criteria. These include all original studies published in English languages that focussed on induced abortion care and assessed women's abortion care experiences and outcomes. After screening for title and abstract and full text, included studies will undergo data extraction, where information relevant to the methodological quality of each study will be collected. This review will integrate qualitative and quantitative data through a narrative synthesis approach. Discussion By synthesising abortion care experiences and outcomes across studies and analysing the commonalities and differences of the multifactorial challenges women face in health facilities, this study will improve the understanding of abortion care experiences and outcomes and inform evidence-based recommendations and future research directions. In addition, this systematic review will also discover and locate an existing measurement tool for abortion care experiences and outcomes for women while receiving the services in the facility.